PENERAPAN STANDAR MUTU PRODUK AIR MINUM ISI ULANG BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DI KECAMATAN BUKITRAYA - Fhatya Amanda Lubis; Rika Lestari; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Water is a basic need that is required by every human being. and function for life. The rapid advancement of technology today raises a variety of new products that can meet consumer needs. Use of technology on the one hand allows manufacturers are able to make a wide range of products. But on the other hand the use of technology allows it produces products that do not conform to cause harm to consumers. One product is a product refill drinking water. depot refill drinking water are industrial enterprises that perform processing of raw water into drinking water and sell directly to consumers. The amount of water depot in the city of Pekanbaru, make it easy for the public also would have a negative impact on people's lives when the review of the relationship between businesses and consumers. In Article 7 letter d BFL No. 8 of 1999 says that the obligation of business is to ensure the quality of goods and / or services produced and / or traded under the provisions of the quality standards of goods and / or services are applicable. One District in the city of Pekanbaru contained drinking water depots Refill adalahKcamatan Bukitraya as much as 37 Depot Water.The issues examined in this research are: First, whether the application of product quality standards refill drinking water in Sub Bukitraya in accordance with the Consumer Protection Act? Secondly, how the impact of product quality standards refill drinking water in Sub Bukitraya ?, Third, How external surveillance efforts undertaken Pekanbaru City Health Office in the application of product quality standards refill drinking water in Sub Bukitraya?This type of research is legal research Sociological. Source of data used are primary data and secondary data, data collection techniques. obtained from questionnaires, interviews and literature study. In this study the authors used a qualitative analysis, in drawing conclusions using inductive method of thinking. Results from this study is the first, the application of product quality standards refill drinking water in Bukitraya in accordance with the Consumer Protection Act. Second. the impact of product quality standards refill drinking water in Bukitraya is the fulfillment of Consumer Rights. Third, efforts undertaken Pekanbaru City Health Office in the application of product quality standards refill drinking water in Sub Bukitraya is to conduct regular senitation. The writer suggests First, business communities Must Maintain Product Quality drinking water refill Secondly, the implementation of quality standards should have a positive impact on the parties, the Third, must made clearer regulation of the health office authority.Keywords: consumer-protection Refill Water-Bukitraya